X-photon 3D lithography by fs-oscillators: wavelength-independent and photoinitiator-free - Dimitra Ladika; Antanas Butkus; Vasileia Melissinaki; Edvinas Skliutas; Elmina Kabouraki; Saulius Juodkazis; Maria Farsari; Mangirdas Malinauskas (Light: Advanced Manufacturing)
Laser direct writing employing multi-photon 3D polymerisation is a scientific and industrial tool used in various fields such as micro-optics, medicine, metamaterials, programmable materials, etc., due to the fusion of high-throughput and fine features down to hundreds of nm. Some limitations of technology applicability emerge from photo-resin properties, however any material modifications can strongly affect its printability, as photoexcitation conditions alter as well. Here we present wavelength-independent 3D polymerisation using low peak power laser oscillators. High pulse repetition rate and fast laser direct writing was employed for advancing additive manufacturing out of the SZ2080TM photo-resist without any photo-initiator. Wavelengths of 517 nm, 780 nm, and 1035 nm are shown to be suitable for producing 300 nm polymerized features even at high – up to 105 µm/s– writing speeds. Variation of organic-inorganic ratio in hybrid material results in shift and decrease of the dynamic fabrication window, yet not prohibiting the photo-structuring. Controlled energy deposition per focal volume is achieved due to localized heating enabling efficient 3D printing. Such spatio-selective photo-chemical cross-linking widens optical manufacturing capacity of non-photo-sensitive materials.